POLIGAMI DAN POLIANDRI DALAM AL-QUR’AN - Maryam Qurotul Aini, Siti (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2020)
Al-Qur'an further regulates the provisions of polygamy which were previously rooted before Islamic society. If previously polygamy could be carried out regardless of the number of wives then with the decline of al-Nisa verse 3, the maximum number of wives in polygamy is four people. The law of polygamy in Islam was originally permissible with the ability to justice, but seeing aspects of goodness and badness, this permissibility becomes an emergency door for conditions to deviate from normal, so that if the government takes part in regulating it then it is as its capacity to regulate the people based on benefit. Whereas the polyandry since the revelation of Surat al-Nisa verse 24, has been a prohibition that must be avoided. If you want to examine further, there are various aspects of benefit in this prohibition